Understanding the challenges of refugee entrepreneurship in tourism and hospitality. Issue 9 (27th July 2019) - Alrawadieh, Zaid; Karayilan, Eyup; Cetin, Gurel
ABSTRACT: In recent years, the refugee crisis has emerged as a major global challenge with social, economic, and political implications. Figures indicate that there are currently over 22 million refugees around the world. While refugees are usually regarded as a burden for their host countries, their entrepreneurial ventures might offer significant contributions to local economies. Although refugee entrepreneurship has become significantly evident in several economies, theoretical and empirical research tackling this issue is still scant. This study aims to explore the characteristics of and challenges faced by refugee tourism and hospitality entrepreneurs in Istanbul, Turkey. Drawing on qualitative data collected through 20 semi-structured interviews with refugee tourism and hospitality entrepreneurs, the findings suggest that refugee entrepreneurs were challenged by four key issues; legislative and administrative, financial, socio-cultural and market-related obstacles. The study also offers insights into characteristics of refugee tourism and hospitality entrepreneurs and their integration into their host communities.